The prevalence and diagnostic criteria of health-care associated infections in neonatal intensive care units in Turkey: A multicenter point- prevalence study - Demirdag, Tugba Bedir; Koc, Esin; Tezer, Hasan; Oguz, Suna; Satar, Mehmet; Saglam, Ozge; Uygun, Saime Sunduz; Onal, Esra; Hirfanoglu, Ibrahim Murat; Tekgunduz, Kadir; Oygur, Nihal; Bulbul, Ali; et al. (ELSEVIER TAIWAN, 2021)
Background: Healthcare-acquired infections (HAIs) in the neonatal period cause substantial morbidity, mortality, and healthcare costs. Our purpose was to determine the prevalence of HAIs, antimicrobial susceptibility of causative agents, and the adaptivity of the Centres for Disease Control and Prevention (CDC) criteria in neonatal HAI diagnosis. Methods: A HAI point prevalence survey was conducted in the neonatal intensive care units (NICUs) of 31 hospitals from different geographic regions in Turkey. Results: The Point HAI prevalence was 7.6\%. Ventilator-associated pneumonia (VAP) and central line-associated bloodstream infections (CLABSI) and late onset sepsis were predominant. The point prevalence of VAP was 2.1\%, and the point prevalence of CLABSI was 1.2\% in our study. The most common causative agents in HAIs were Gram-negative rods (43.0\%), and the most common agent was Klebsiella spp (24.6\%)

81.2\% of these species were extended spectrum beta-lactamase (ESBL) (\& thorn

). Blood culture positivity was seen in 33.3\% of samples taken from the umbilical venous catheter, whereas 0.9\% of samples of peripherally inserted central catheters (PICCs) were positive. In our study, 60\% of patients who had culture positivity in endotracheal aspirate or who had purulent endotracheal secretions did not have any daily FiO2 change (p = 0.67) and also 80\% did not have any increase in positive end-expiratory pressure (PEEP) (p = 0.7). On the other hand, 18.1\% of patients who had clinical deterioration compatible with VAP did not have endotracheal culture positivity (p = 0.005). Conclusions: Neonatal HAIs are frequent adverse events in district and regional hospitals. This at-risk population should be prioritized for HAI surveillance and prevention programs through improved infection prevention practices, and hand hygiene compliance should be conducted. CDC diagnostic criteria are not sufficient for NICUs. Future studies are warranted for the diagnosis of HAIs in NICUs.
Keywords: health-care associated infection; neonate; point prevalence; surveillance